1997
DOI: 10.1677/jme.0.0180137
|View full text |Cite
|
Sign up to set email alerts
|

Action of peripheral or intrathyroidal lymphocytes on autologous thyrocytes cultured in follicles in collagen gel

Abstract: We have studied the action of peripheral blood lymphocytes (PBLs) and intrathyroidal lymphocytes (ITLs) on the biochemical and hormonal metabolism of autologous thyrocytes cultured in follicles in a collagen gel. The production of tumour necrosis factor alpha (TNF-alpha) in culture was also measured. Thyroid tissues and lymphocytes were obtained from ten patients with Graves' disease and from five control subjects. Lymphocyte-induced cytotoxicity was evaluated in autologous thyrocytes cultured in a collagen ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Studies suggest that increases in endogenous TNFa production may be involved in the regulation of thyroid function in ATD. That is, TNFa and TNFa mRNA are found in human thyroid tissues from patients with Graves' disease and Hashimoto's thyroiditis (1)(2)(3)(4). In FRTL-5 cells, we (5,6) and others (7)(8)(9)(10) have observed that TNFa inhibits type I 5 0 -deiodinase activity and thyroglobulin (Tg), thyroid peroxidase (TPO) and type I 5 0 -deiodinase gene expression.…”
Section: Introductionmentioning
confidence: 92%
“…Studies suggest that increases in endogenous TNFa production may be involved in the regulation of thyroid function in ATD. That is, TNFa and TNFa mRNA are found in human thyroid tissues from patients with Graves' disease and Hashimoto's thyroiditis (1)(2)(3)(4). In FRTL-5 cells, we (5,6) and others (7)(8)(9)(10) have observed that TNFa inhibits type I 5 0 -deiodinase activity and thyroglobulin (Tg), thyroid peroxidase (TPO) and type I 5 0 -deiodinase gene expression.…”
Section: Introductionmentioning
confidence: 92%
“…The interactions between thyrocytes and these cell types are thus expected to be involved in the stability and regulation of thyrocyte growth and differentiation. But the intercommunications within the thyroid are poorly defined 47–52 . The capturing ability of the 3‐D collagen gel culture system makes it easy to carry out stable cocultures of various cell types.…”
Section: Thyrocyte Integration In a 3‐d Collagen Gel Culture Systemmentioning
confidence: 99%
“…Our results showed that if culture was begun with closed follicles then extracellular matrix support elements were not required [56,57,79,80] nor was TSH for maintaining follicular cavity, as has been described in most pseudofollicle or follicle cultures reconstructed from monolayers, or similar structures called "follicles" [57,50,60,61,62,79,96], thereby demonstrating that if closed follicles are used from the start of culture they conserve their morphology, having the correct polarity as that of their thyrocytes in culture and have a binding complex (tight junction, belt desmosome and spot desmosome) in lateral membranes' apical part as well as in vivo [9]. Such closed follicles in culture responded to TSH, like other in vitro models [42] or like gland follicles in normal in vivo to TSH stimulus [3,25], epithelium thickness, RER and GC becoming increased, and follicular cavities becoming notably reduced [11,83,90].…”
Section: Morphological Studymentioning
confidence: 81%
“…It is so important that specific genes have been described which govern follicle formation and maintain follicle architecture, the gene transcribing the thyroid-specific enhancerbinding protein (T/ebp or Nkx2.1) regulating the transcription of genes implicated in hormone synthesis: NIS, TPO, TSH receptor and Tg and re-organised transfecteds thyrocites in follicles [78]. Human goitre follicle structure has been covered with collagen to preserve it longer and cavities in human [79,80] and mouse thyrocyte [78] thin cell bilayers have persisted 2 days more. Collagen's importance in preserving epithelial cells' apical-basal polarity has been described for obtaining MDKC (Madin-Darby canine kidney epithelial cell line) cell 3D cultures, but hepatic growth factor (HGF) was added to cultures [81].…”
Section: Folliclesmentioning
confidence: 99%
See 1 more Smart Citation